Estabilidade térmica do eletrodo positivo LiCr(MoO4)2 para baterias de íon de lítio - Santos, Mariana Oliveira dos (2023)
The popularization of electric vehicles (EVs) depends on pending improvements in the safety, cost, and energy density of lithium-ion batteries (LIBs). A crucial component to this is the positive electrode since its active material decomposes if heated 'charged', releasing oxygen – which can trigger electrolyte combustion and cause fires – and it also contains cobalt, costly metal. Given this scenario, this work investigated the high-temperature thermal stability of LiCr(MoO4)2, an active cobalt-free material with a high specific capacity. The material was synthesized by solid-state reaction preceded by wet milling and characterized by x-ray diffraction (XRD), Raman spectroscopy and scanning electron microscopy, where the effect of heating the material (which is synthesized already in the 'charged' state) in two different environments was compared: one in air, with the material alone; and another in argon atmosphere, with the material as a component of the slurry (active material + PVdF + conductive carbon) that is used in the electrode, simulating the environment to which the active material is exposed inside the battery. The obtained material has space group P1̅, in agreement with the literature, and particle size in the 0.4 – 7 μm range. XRD and Raman results showed that it remains stable in the air throughout the investigated temperature range (300 K - 973 K), i.e., it neither undergoes structural phase transition nor decomposition. In this range, it showed negative thermal expansion (NTE) along the b-axis due to MoO4 tetrahedra rotation; the coefficient of thermal expansion along the a-axis remained approximately constant at 10 × 10-6 K-1, while the b- and c-axis coefficients were in the ranges -2 to -15 × 10-6 K-1and 30 to 55 × 10-6 K-1, respectively. As a slurry component, when heated in an argon atmosphere, it undergoes chemical attack from pyrolysis products of PVdF and starts to decompose at ~450 °C, more than 100 °C above the decomposition temperature of commercial positive electrodes NCA, LCO and NMC. Thus, LiCr(MoO4)2 has higher safety than 3 of the 4 major commercial positive electrodes (with only LFP as an exception) and is, therefore, a promising candidate for application as a positive electrode in LIBs.